Is the assumption of waning of treatment effect applied consistently across NICE technology appraisals? A case-study focusing on disease-modifying therapies for treatment of multiple sclerosis. (13th December 2022) - Armoiry, Xavier; Wang-Steverding, Xia; Connock, Martin; Grove, Amy; Clarke, Aileen; Arun, Tarunya; Counsell, Carl; Auguste, Peter
Abstract: Objectives: Whether the effects of therapies may wane over time is a matter of debate, especially when considering their long-term cost-effectiveness. Here, we examined how the assumption of the waning of treatment effect was applied across the National Institute for Health and Care Excellence (NICE) appraisals for disease-modifying therapies (DMTs) used in multiple sclerosis. Methods: We undertook a document analysis following a search of the NICE website. The inclusion criteria of the study were as follows: all publicly available documents related to completed appraisals for DMTs (period: January 2000 to July 2021). The exclusion criteria of the study were as follows: all documents that did not meet the inclusion criteria, especially pertaining to drugs used in other disease areas. We extracted information about the waning of treatment effect assumption as considered by companies, assessment groups, and appraisal committees, and we analyzed trends over time. Results: We reviewed fifteen appraisals that reported guidance on sixteen DMTs. Irrespective of the drugs' mechanism of action or their pharmaceutical nature, there was substantial variation in the modalities when the assumption of waning was implemented. We noted the recent preference to use all-cause discontinuation as a proxy. This heterogeneity did not appear to affect acceptance of the DMTs (all but one were recommended for use across the National Health System (NHS)). Conclusions: Modeling the long-term effect of therapies is challenging, especially given the limited follow-up duration of related trials. This generates recurrent debates on the presence of waning of treatment efficacy and heterogeneity across appraisals. More refined recommendations obtained by consensus among stakeholders could help to achieve greater consistency in decision making.